A Review on Flavonoids as Anti-Helicobacter pylori Agents - Aditya Tan; Katia Castanho Scortecci; Fabio Boylan (Applied Sciences)
Helicobacter pylori is a Gram-negative bacterium from the Epsilonproteobacteria class, associated with various gastric diseases, including gastric cancer. It infects both adults and children, with a high prevalence in developing countries due to poor health conditions. The International Agency for Research on Cancer has classified H. pylori as a class I carcinogen, linked not only to gastric cancer but also to neurological disorders. Current treatment involves proton pump inhibitors combined with antibiotics for 10 to 14 days, but patient non-compliance can lead to increased antibiotic resistance. This review examines studies from the past decade that explore flavonoids as potential future treatments for H. pylori. Flavonoids like kaempferol, rutin, quercetin, myricetin, catechin, epicatechin, eupatilin, chrysin, apigenin, and hesperetin have been shown to regulate the expression of key H. pylori genes, alter cell membrane permeability, and affect proton efflux. These biomolecules, found in various plants, have demonstrated the potential to inhibit H. pylori, even in resistant strains. Gene expression and molecular docking studies reveal how these flavonoids interact with the membrane, bacterial genes, and proteins, affecting host cell transcription, translation, and bacterial adherence. While promising, clinical trials are needed to better understand their mechanisms and efficacy.